Head Shape Variation in Cnaphalocrocismedinalis (Guenee) Larvae Associated with Different Rice Varieties (Journal of Informatics and Mathematical Sciences, 2017)
Cnaphalocrosismedinalis is considered a dominant insect pest of rice throughout the rice growing areas in the Philippines. Its head, a morphological trait, is specialized for food gathering and manipulation, including its relation to bite performance and ecology has been used for investigating the integration of different phenotypic components. Because of the role of this structure in the insect pest, we quantitatively describe the amount of morphometric variation between populations of the pest collected from different rice hosts. Landmark-based geometric morphometrics method was used to quantify and analyze head shape variation by the application of statistical methods of the relative warp scores. Based on the results of the assessment, significant variations in head shapes between populations of the insect were observed and argued to be due to the selection exerted by the host.
Keywords: Rice leaf; Cnaphalocrosismedinalis